ADMINISTRATIVE ASPECTS OF OBTAINING FIREARM LICENCES IN REPUBLIC OF SRPSKA - Miljić, Dražen (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2025)
Abstract: Due to the widespread misuse of firearms, both legally acquired and illegal, the interest of the scientific and professional public and citizens of the Republic of Srpska in the method of obtaining a permit and the number of persons who own firearms is justified. The paper will analyze the administrative procedure for obtaining a permit to own firearms and the actions of the competent authorities with the aim of revealing shortcomings in the regulation of the matter and shortcomings in resolving this type of administrative matters.Firearms have major implications for the security of citizens of the Republika Srpska, especially recently, when the number of crimes where firearms are the main instrument of the perpetrator is increasing. Finally, which speaks in favor of the neglect of this important topic, we emphasize that during our research we did not come across a single work written on this topic in the Republika Srpska.
Keywords: firearms; administrative procedure; security; discretionary assessment; Ministry of the Interior of the Republika Srpska